TINGKAH LAKU BERTELUR BURUNG MALEO (Macrocephalon maleo) DI MUARA PUSIAN KAWASAN TAMAN NASIONAL BOGANI NANI WARTABONE KECAMATAN DUMOGA TIMUR KABUPATEN BOLAANG MONGONDOW - Poli, Zibran; Polii, Bobby; Paputungan, Umar (Universitas Sam Ratulangi, 2016)
EGG LAYING BEHAVIOR OF MALEO BIRD (Macrocephalon maleo) AT MUARA PUSIAN NATURAL CONSER-VATION IN BOGANI NANI WARTA-BONE NATIONAL PARK, EAST DUMO-GA DISTRICT OF BOLAANG MONGON-DOW REGENCY Bogani Nani Wartabone National Park was conservation living area of the all flora and fauna species including maleo bird (Macrocephalon maleo) as the endemic bird in Sulawesi Island. Objective of this research was to study behavioral laying egg of maleo bird, temperature and hole deep of laying egg, total visitation of maleo bird at laying egg hole places and predator threat around laying egg hole places. Research was conducted by direct observation at the maleo habitat of laying egg holes place. Data obtained were analyzed descriptively to describe the facts and phenomena occurring at the bird habitat. Results showed that bird activities before laying egg at holes included digging the laying egg hole, laying egg in the hole, heaping up egg hole, digging false egg holes. Bird activities after laying egg at holes included pause and look for feed around holes and then they flied to the forest area. The average times of laying egg were 1 to 3 hours, started from looking for area of hole, digging holes, playing around egg holes area to the end of laying egg in the hole. The averages of egg holes deep were 41.8 Â± 14.28 cm and egg holes temperatures were 270 C - 340 C. Maleo birds were laying their eggs more around Tower I compared with around Tower II. Around Tower I had dense vegetation of trees used as shelter, protection place from predators, clean area from scrubs for easy digging holes of laying egg. Around Tower II, there were growing scrubs (Saccharum spontaneum) and coarse grass (Imperata cylindrical) causing unsecure and difficult digging holes by maleo birds in laying their eggs. The total visitations of maleo birds around egg holes areas were visibly observed of 28 pairs and 1 male without spouse and 9 pairs found by auditory observation. Therefore, there were 37 pairs consisted of 37 females and 38 males of maleo birds observed. The total eggs obtained during observation were 42 eggs, consisted of 2 damaged eggs and 40 hatching eggs using the artificial hatchery at study location. Key words: Behavioral laying egg, maleo bird (Macrocephalon maleo).